Global phylogeography and genetic characterization of carbapenem and ceftazidime-avibactam resistant KPC-33-producing Pseudomonas aeruginosa - Longjie Zhou; Jiayao Yao; Ying Zhang; Xiaofan Zhang; Yueyue Hu; Haiyang Liu; Jintao He; Yunsong Yu; Minhua Chen; Yuexing Tu; Xi Li (npj Antimicrobials and Resistance)
Abstract Ceftazidime-avibactam (CZA) is currently one of the last resorts used to treat infections caused by carbapenem-resistant Enterobacteriaceae and Pseudomonas aeruginosa. However, KPC variants have become the main mechanism mediating CZA resistance in KPC-producing gram-negative bacteria after increasing the application of CZA. Our previous study revealed that CZA-resistant KPC-33 had emerged in carbapenem-resistant P. aeruginosa (CRPA) and had resulted in death due to hypervirulence and extensive drug resistance; however, the evolutionary path of KPC-33-producing CRPA has not been investigated. Here, we observed the emergence of bla KPC-33 in CRPA under drug pressure, leading to resistance to CZA. We further elucidated the pathway of resistance development due to bla KPC mutations in P. aeruginosa. Three KPC-producing P. aeruginosa (KPC-PA) strains (including one bla KPC-33-positive strain and two bla KPC-2-positive strains) were successively isolated from a hospitalized patient. The bla KPC-33-positive CZA-resistant strain SRPA0656 (CZA MIC >128 μg/mL, imipenem MIC = 32 μg/mL) was isolated after the bla KPC-2-positive P. aeruginosa SRP2863 (CZA MIC = 1 μg/mL, imipenem MIC >128 μg/mL) was treated with CZA. The subsequent use of carbapenems to treat the infection led to the re-emergence of the KPC-2-producing strain SRPA3703. Additionally, we collected four other KPC-33-producing P. aeruginosa strains. Antimicrobial susceptibility testing revealed that all the KPC-33-bearing P. aeruginosa strains in this study were multidrug-resistant but susceptible to colistin and amikacin. Whole-genome sequencing indicated that bla KPC-33 was located on two Tn4401-like transposons contained in the plasmids and that most of these plasmids could be transferred into P. aeruginosa PAO1Rif isolates. Growth rate determination demonstrated that the relative growth rate of P. aeruginosa harboring bla KPC-33 was faster than that of P. aeruginosa harboring bla KPC-2 in the logarithmic phase. Global phylogenetic analysis revealed that most KPC-PA strains were isolated from China and the USA. MLST revealed that the most common ST in KPC-PA was ST463, which was detected only in China, and that all the strains carried bla KPC-2 or its derivatives. These results indicated that the use of CZA for the treatment of KPC-2-producing P. aeruginosa may have contributed to the evolution of KPC-33. The widespread dissemination of KPC-PA (especially the ST463) and Tn4401 transposons may increase the spread of CRPA isolates carrying bla KPC-33. Close attention to the development of resistance to CZA during clinical treatment of CRPA infection and monitoring CZA-resistant strains is necessary to prevent further spread.